Importância da gestão no uso das marcas, como estratégia de empresas de pequeno e médio porte: estudo de caso em uma organização de Belo Horizonte - MG - Camilla Baggio de Santa Anna (2017)
The present dissertation aims to verify how the management of intellectual property, more specifically the brands, has been carried out bysmall and medium-sized companies. Thus, it aims to analyze the possible advantages and difficulties that entrepreneurs find in the market, when the subject is management of their intangibles. This paper presents a study on the institute of trademarks (its concepts, types, classes, registration procedure, legislation, litigation and others), intellectual property management in general and notions of business strategy. The study is part of the area of intellectual property concentration, specifically in trademark Law and seeks to highlight good practices for its management of this right, considering the challenge that small companies in Brazil have in the management of their assets. intellectual property. This study is important in view of the scope that the theme has been assuming in the development of the countries, in a scenario of globalization of the markets, in which the brands can contribute greatly to the competitive advantages and the economic development coming from innovations. In addition, it is useful for smaller companies, which are dealing with intellectual property assets, to be able to base themselves to adopt better management practices of their intangibles in the quest for greater competitiveness. Finally, the paper aims to identify, as a mining company the follow-up paper and pulp works with its intangible rights. A case study was carried out with a medium-sized company from Belo Horizonte MG, from which it can be verified as a result that the company performs a reasonable articulation of its assets in relation to the resources it has, the difficulties related to its size, Environment and the competitive standards of the paper packaging industry. The case describes positive and negative aspects of the management used by such Organization, for one of its brands, aiming the defense of this, including in Judgment. The conclusion brings, in the end, the importance of the work for marking protection, either in the administrative or judicial scenario, mainly, for smaller companies.